Metarepresentation : a relevance-theory approach - Noh, Eun-Ju. (Amsterdam ; Philadelphia, PA : John Benjamins Pub., 2000)
Eun-Ju Noh's book provides a close look at linguistic metarepresentation showing how beliefs, utterances, and propositions are represented and how they are inferred. The author explains how metarepresentation works in various types of uses: quotations, negation, echo questions, and conditionals in terms of truth conditions and pragmatic enrichment. Ample examples are provided from the English language. The relevance-theory approach gives room for extralinguistic parameters to be considered, and suggestions are made for further research in cross-linguistic studies and metarepresentation.
Introduction: Metarepresentation in Communication -- Ch. 1. Analyses of Quotation -- Ch. 2. Relevance Theory and Metarepresentational Use -- Ch. 3. Metalinguistic Negation -- Ch. 4. Echo Questions -- Ch. 5. Metarepresentational Uses in Conditionals.
Includes bibliographical references (pages 221-236) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Semantics; Quotation; Grammar, Comparative and general -- Indirect discourse; Relevance; Sémantique.; Citation; Discours indirect; Pertinence; semantics; LANGUAGE ARTS & DISCIPLINES -- General; Grammar, Comparative and general -- Indirect discourse; Quotation; Relevance; Semantics; Electronic book